Young tennis players and balance performance - Malliou, V. J.; Beneka, A. G.; Gioftsidou, A. F.; Malliou, P. K.; Kallistratos, E.; Pafis, G. K.; Katsikas, C. A.; Douvis, S. (The Journal of Strength and Conditioning Research, 2010)
The purpose of the present study was to investigate the effect of a tennis training session on the balance performance of young tennis players. The study was conducted on 36 elite tennis players (age 14 ± 2 years; body mass 55 ± 6 kg; body height 165± 6 cm; mean ± SD) participating in the national young tennis championship. Balance performance was assessed before and immediately after a tennis training session (pre-training and post-training, respectively). The balance assessment was performed with 2 different balance boards and the Biodex Stability System. In addition, dynamometric measurements of peak isokinetic moment in the knee flexors and extensors were performed pre and post tennis training session, to quantify the degree of muscle fatigue induced by the tennis training session. One-way analysis of variance with repeated measures was used to test for differences in balance performance and in isokinetic performance between pre and post tennis training session. The data analysis revealed no significant differences (p > 0.05) in balance performance, whereas there were significant differences in knee joint moment production between pre and post tennis training measures. Although the tennis training session of the present study had no significant effect (p > 0.05) on any of the balance performance indicators examined, there was a decline in balance performance, which suggests that different level of fatigue for an extended period (games) will have greater effect on balance performance. It is suggested that a tennis-specific balance exercise program should be included in the tennis training session.